Fuel cell catalyst coating quality for reliable ex-situ ORR activity results - Mårtensson, Hugo (My University, 2025)
Proton exchange membrane fuel cells (PEMFCs) are energy conversion devices that could play a key role in the reduction of greenhouse gas emissions. However, one major problem for PEMFCs is the slow oxygen reduction reaction (ORR), which causes large overpotentials and requires a large amount of expensive platinum catalyst to be sped up. For that reason, evaluation of the ORR activity of catalysts is important, and the rotating disk electrode (RDE) method is commonly used for this purpose. However, there are still problems with achieving reliable results of the ORR activity with RDE, specifically due to the activity’s dependence on the quality of the catalyst coating on the electrode. This thesis investigates how different parameters of a catalyst ink influence the catalyst coating and how to achieve a uniform thin coating. For one catalyst, inks with different alcohol contents and platinum loadings were tested, and for a second catalyst, different alcohol contents and pH levels were tested. The alcohol content did not appear to have a significant impact on the ORR activity or the homogeneity of the thin films. A high alcohol content facilitated the spreading out of the ink due to a lower surface tension, but it was also harder to keep it from spreading outside the electrode disk. With platinum loading, there seemed to be a lower limit between 10 and 20 μgPt/cm2 for the catalyst to cover the entire disk homogenously. Below this limit, the mean specific ORR activity was about 20% lower. At 34.8 μgPt/cm2, the results were about the same as for 20 μgPt/cm2, meaning no upper limit appears to have been reached. For the second catalyst, stability issues were observed, which did not significantly change with the alcohol content. Increasing the pH of the ink by adding KOH improved ink stability, but it was still not possible to produce a completely homogeneous coating. Further investigations on how to achieve a homogeneous coating with this catalyst are therefore needed.
Keywords: Proton exchange membrane fuel cell, oxygen reduction reaction, rotating disk electrode, Pt/C catalyst